2004
DOI: 10.1007/s00213-004-2027-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential dopaminergic modulation of executive control in healthy subjects

Abstract: Our findings suggest that dopamine agonists modulate two EC tasks differently. Furthermore, there seems to be a selective modulation of different aspects of the Stroop task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 53 publications
(67 reference statements)
2
41
1
1
Order By: Relevance
“…The improved Stroop performance following dopamine depletion (like serotonin depletion) suggests greater attentional control, as these effects were observed independent of effects on general speed of information processing (ie, overall reaction time). These findings are somewhat contrary to the findings of Roesch-Ely et al (2005) who found decreased Stroop interference with stimulation of D 2 receptors. These findings are also contrary to molecular imaging studies (ie, PET Imaging with [ 18 F]FDOPA) in which a negative association between regional [ 18 F]FDOPA uptake (a measure of dopamine synthesis) and Stroop interference has been found in normal control subjects and patients with Parkinson's disease and schizophrenia (Bruck et al, 2005(Bruck et al, , 2001McGowan et al, 2004).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The improved Stroop performance following dopamine depletion (like serotonin depletion) suggests greater attentional control, as these effects were observed independent of effects on general speed of information processing (ie, overall reaction time). These findings are somewhat contrary to the findings of Roesch-Ely et al (2005) who found decreased Stroop interference with stimulation of D 2 receptors. These findings are also contrary to molecular imaging studies (ie, PET Imaging with [ 18 F]FDOPA) in which a negative association between regional [ 18 F]FDOPA uptake (a measure of dopamine synthesis) and Stroop interference has been found in normal control subjects and patients with Parkinson's disease and schizophrenia (Bruck et al, 2005(Bruck et al, , 2001McGowan et al, 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Obviously this would have hindered our ability to detect any changes in Stroop facilitation under the different treatment conditions, although previous studies have also not found any changes in facilitation following dopaminergic or serotonergic modulation (Roesch-Ely et al, 2005;Schmitt et al, 2000). Despite this, future research may consider using faster stimulus presentation, or a larger sample size, in order to reproduce this phenomenon of facilitation (Barch et al, 2004), and to extend our observations.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations